Revitalizing green economic capability to maintain the financial stability of MSMEs in Bira Beach - Sharon, ST Salmah; Monalisa, Monalisa; Muchtar, Muchtar; Firman, Afrizal; Basir, Mustika Kusuma; Arif, Muh (Universitas Muhammadiyah Yogyakarta, 2025)
To maintain the financial stability of Micro, Small and Medium Enterprises (MSMEs) is a vital issue which needs a revitalization of green economic capability. This study explores the impact of Green Economy Capability (GEC) on the financial stability of MSMEs in the coastal region of Bira Beach, with a focus on the mediating role of government support. A SmartPLS-SEM used in this study to investigate the survey involving 150 MSMEs. The key variables measured include GEC, financial stability, and government support, with the data analyzed through descriptive and inferential statistical techniques. The findings indicate that GEC significantly influences government support, which in turn has a positive effect on financial stability. However, GEC does not have a direct impact on MSMEs' financial stability. These findings underscore the critical role of government policies in supporting the adoption of sustainable practices among MSMEs, particularly in regions heavily dependent on tourism. This research contributes to the literature by providing empirical evidence of the indirect relationship between GEC and financial stability through government support in the coastal MSME sector. In results, we offered two solutions. First, the policymakers must prioritize initiatives that strengthen MSME’s capacity for sustainable practices. Second, the need for tailored support systems in coastal areas like the adoption of green practices which must be integrated with local economic strategies to yield both environmental and financial benefits.